Застосування сучасних технологій при розробці карткових настільних ігор - Ісаєнко, Т. (My University, 2020)
Making your own card game is much harder than it looks at first glance. And much more interesting than it seems. That is, to make the design of the game is not difficult, but to make interesting and playable, not plagiarism – is not at all simple. It is necessary to take into account all the features of the consumer: age, social level
Keywords: карткові настільні ігри; технологічний процес; qr-код